Pelatihan Pembuktian Perselisihan Hasil Pemilu Di Kota Bengkulu - Amancik, Amancik; Ahmad Saifulloh, Putra Perdana; Illahi , Beni Kurnia; Barus, Sonia Ivana (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2021)
The Constitutional Court has the authority to protect the constitutional rights of citizens and provide interpretations of the constitution, ideally in an election which is a political contestation that is built up by many things in its implementation. The Constitutional Court's function is to keep the Election in line with Election Principles which are regulated by Positive Law. Based on the above assumptions, it is worth discussing whether the process of proving PHPU in the Constitutional Court has been able to guarantee the implementation of an overly judicial election, or simply whether the proof of PHPU is ideal. This activity is about providing understanding to Participants of Evidence and Evidence Tool on Election Result Disputes; Providing understanding to Participants regarding updated matters regarding the Legal Evidence of Election Result Dispute; and especially for Lecturers as a means of Community Service which is part of the Tri Dharma of Higher Education. Keywords: Evidence, Evidence Tool, Election Result Disputes Abstrak Mahkamah Konstitusi memiliki kewenangan untuk melindungi hak konstitusional warga negara dan memberikan interpretasi terhadap konstitusi, idealnya dalam Pemilu yang merupakan kontestasi politik dipengaruhi oleh banyak hal dalam pelaksanaanya. MK berfungsi untuk menjaga agar Pemilu sejalan dengan Asas Luber dan Jurdil sebagaimana yang diatur Hukum Positif. Berdasar pada anggapan di atas, maka patutlah didiskusikan, apakah proses pembuktian PHPU di MK telah mampu menjamin terlaksanya Pemilu yang Luber Jurdil, atau sederhananya apakah Pembuktian PHPU tersebut telah ideal. Kegiatan ini dimaksudkan untuk memberikan pemahaman kepada Peserta tentang Pembuktian dan Alat Bukti Perselisihan Hasil Pemilu; Memberi pemahaman kepada Peserta tentang hal-hal update tentang Pembuktian Hukum Acara PHPU; dan khusus Dosen sebagai sarana Pengabdian Kepada Masyarakat yang merupakan bagian dari Tri Dharma Perguruan Tinggi. Kata kunci: Pembuktian, Alat Bukti, Perselisihan Hasil Pemilu